PRODUKTIVITAS KARET PADA LAHAN HKM JAYA LESTARI KABUPATEN WAY KANAN PROVINSI LAMPUNG - -, Supriadi; Riniarti, Melya; Bahri, Samsul (Universitas Gorontalo, 2018)
Rubber was one of favorite multipurpose tree species which planted by community forest, since its produced latex with high value. Jaya Lestari community forest was located on Mananga Jaya Village, Way Kanan District, Lampung Province. This research aimed to collect data’s of rubber productivity based on plant age in Jaya Lestari community forest areas. Research conducted by interview 230 household. The result showed that rubber harvested since 6 years old. The productivity rate increased until 25 years old than decreased gradually. The highest productivity was 2,5 tone/ha/years on ten years old rubber. In average farmer had 0,1—2 ha rubber plantation, with plant distance were 4 x 6 m.